2016
DOI: 10.1111/nph.14314
|View full text |Cite
|
Sign up to set email alerts
|

A nonnative and a native fungal plant pathogen similarly stimulate ectomycorrhizal development but are perceived differently by a fungal symbiont

Abstract: The effects of plant symbionts on host defence responses against pathogens have been extensively documented, but little is known about the impact of pathogens on the symbiosis and if such an impact may differ for nonnative and native pathogens. Here, this issue was addressed in a study of the model system comprising Pinus pinea, its ectomycorrhizal symbiont Tuber borchii, and the nonnative and native pathogens Heterobasidion irregulare and Heterobasidion annosum, respectively. In a 6-month inoculation experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…The pine trees included in the study of Zampieri et al . () showed a strong decline in vitality just a few months after inoculation. At the same time, sampled spruce trees showed no symptoms of infection except for the heartwood decays, which could be observed only after the tree was felled.…”
Section: Occurrence Of Heterobasidion In Sampled Treesmentioning
confidence: 99%
See 1 more Smart Citation
“…The pine trees included in the study of Zampieri et al . () showed a strong decline in vitality just a few months after inoculation. At the same time, sampled spruce trees showed no symptoms of infection except for the heartwood decays, which could be observed only after the tree was felled.…”
Section: Occurrence Of Heterobasidion In Sampled Treesmentioning
confidence: 99%
“…These results indicate that Heterobasidion infection has an effect on the fungal communities in the parts of the tree adjacent to the tissues colonized by the pathogen, with no significant effect on more distant regions. However, it was demonstrated recently that the Heterobasidion infection promotes mycorrhiza development in Pinus pinea (Zampieri et al ., ), indicating that Heterobasidion infection might have a more profound effects on the fungal communities inhabiting the infected tree. Several explanations could be proposed for the lack of significant differences in the structure of root fungal communities associated with asymptomatic and symptomatic spruce trees in our experiment.…”
Section: Occurrence Of Heterobasidion In Sampled Treesmentioning
confidence: 99%
“…Inoculation experiments have shown that plant responses to N enrichment are more positive in the presence of DSE than in their absence (reviewed by Jumpponen et al., ), suggesting that these fungi can become more beneficial to plants under N enrichment. But complex interactions between fungal guilds have also been observed, for example, mycorrhizal and DSE colonization can reduce colonization by pathogens, and colonization by pathogens can enhance mycorrhizal colonization (Laliberté, Lambers, Burgess, & Wright, ; Maherali & Klironomos, ; Mandyam & Jumpponen, ; Newsham, Fitter, & Watkinson, ; Sikes, Cottenie, & Klironomos, ; Zampieri et al., ). As a result, plant growth responses to N enrichment could be the outcomes of both direct effects of fungal guilds and indirect effects derived from interactions between fungal guilds.…”
Section: Introductionmentioning
confidence: 99%
“…A few comparative studies have elucidated key traits of the biology and epidemiology of H. irregulare in Italy including one focusing on its impact and interaction with native microbes symbiotic to host plants (Zampieri et al, 2017). However, very little is known about the potential effects of the direct interaction between the two fungal pathogens on their respective fitness and hybridization potentials.…”
Section: Introductionmentioning
confidence: 99%